2015
DOI: 10.3892/or.2015.4272
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin 1 is involved in survival, proliferation and carcinogenesis of pancreatic cancer

Abstract: Abstract. Pancreatic cancer (PCC) is one of the most difficult cancers to treat and the 10th leading cause of cancer-related death in worldwide. Studies have demonstrated that the tetraspanin 1 (Tspan1) is overexpressed in various cancers and may be a potential therapeutic strategy for the treatment of different cancers. However, the possible role of Tspan1 in PCC is still unknown. In the present study, our data revealed that the increased Tspan1 in PCC tissues was associated with the clinicopathological featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…TSPANs are a large family of four-pass transmembrane proteins that are ubiquitously expressed in mammals, and emerging evidence supports their crucial role in human cancer [32]. Since TSPANs were first identified in human leukocytes, numerous studies reported that their expression correlates with tumor type, stage, and clinical outcome of patients [33].…”
Section: E C Bmentioning
confidence: 99%
“…TSPANs are a large family of four-pass transmembrane proteins that are ubiquitously expressed in mammals, and emerging evidence supports their crucial role in human cancer [32]. Since TSPANs were first identified in human leukocytes, numerous studies reported that their expression correlates with tumor type, stage, and clinical outcome of patients [33].…”
Section: E C Bmentioning
confidence: 99%
“…Quantitative PCR of miRNA was performed using an Applied Biosystems 7300 Sequence Detection system. The 10 µl PCR reaction contained 0.67 µl reverse transcription product, 1X TaqMan Universal PCR Master Mix, and 1 µl of the primer and probe mix, according to the TaqMan MicroRNA assay protocol (Applied Biosystems) (16). The relative expression levels of genes were determined using the 2 -∆∆Ct analysis method.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Characterization of these mutants revealed an involvement of plant TETs in the control of cell proliferation, cell differentiation and cell identity, as well as tissue patterning. Such developmentally important functions have been described for tetraspanins earlier in other model organisms (Kazarov et al, 2002; Hemler, 2008; Franco et al, 2010; Anderson et al, 2011; Hou et al, 2015), suggesting that TET functions are partially conserved between kingdoms.…”
Section: Tetraspanin Mutants In Plantsmentioning
confidence: 53%